Formulation of thermoresponsive and buccal adhesive in situ gel for treatment of oral thrush containing poorly water soluble drug bifonazole - Dimendra Patel; Dipti Patel; Jatin Prajapati; Umang Patel; Vijay Patel (Wolters Kluwer Medknow Publications, 2012)
The aim of the present work is to formulate and evaluate in situ oral topical gels of poorly water soluble drug Bifonazole based on temperature induced systems for the treatment of oral candidiasis. Bifonazole is poorly water soluble and low permeable drug means it's belongs to BCS Class IV. Due to its poor water solubility, it necessary to enhance solubility in water by make complex with Beta- Cyclodextrin (Drug to βCyclo Dextrine ratio is 1:1). After in situ gel preparation done by using Poloxamer (10% and 15%w/w) along with carbopol 934 (0.2 to 1.0% w/w) and Bifonazole - β CD complex (1%w/w). The formulations were evaluated for physiochemical parameter, gelation Temperature, viscosity, gel strength, content uniformity mucoadhesive force, Diffusion Study.